Recalcitrant solar urticaria induced by UVA and visible light: A case report - Metavee Insawang (2018)
A 41 year-old man presented with a ten-year history of recurrent erythema and swelling of skin that occurred following sun exposure even as little as ten minutes. The lesion affected only on the sun exposed area. A phototesting was carried out and revealed that urticaria was induced following ultraviolet A (UVA) and visible light exposure. Solar urticaria (SU) from UVA and visible light was diagnosed. Many treatment options including combination of oral antihistamines, psoralen plus UVA (PUVA) photochemotherapy, narrowband UVB (NBUVB, 311 nm) phototherapy, and plasmapheresis were tried in the presented patient without significant response. Although various treatments are available, managing SU remains a challenging problem in many patients.